Customer satisfaction toward Menara Taming Sari: a study at Melaka Taming Sari Berhad / Roselini Jusoh - Jusoh, Roselini (2009)
The objective of all marketing efforts should be to maximize customer satisfaction. Marketers must be certain to provide the best possible product for the money and to avoid raising consumer expectations for product or services like Taming Sari performance beyond what the product or services can deliver. Marketers want to deliver more than customers expect. In term of marketing program for Taming Sari Berhad is under the responsibility of their marketing and sales department under supervision of Mr. Mohd Husni Husin. Marketing department is responsible to increase awareness, sales and also customer satisfaction toward Taming Sari tower. Customer satisfaction is often defined as a measure of how total product or service performs in relation to a set of customer expectation requirement. The customer is satisfied and delighted if the product or service performance matches their expectations. Thus, satisfaction is often measured as a function of perceived performance and expectations. If the performances exceed expectations, the customers are highly satisfied or delighted. Improving customer satisfaction can come from a variety of activities. The existing evidence suggest that major gains in customer satisfaction are come from improvement in service quality, service feature and customer complaint handling. Those factors are important in facilitating the business of achieving customer satisfaction and loyalty.